Thermoelectric properties of n-type Bi2Te3 alloys produced by a combined process of magnetic pulsed compaction (MPC) and spark plasma sintering (SPS) - Lee, Chul-Hee; Fatih Kilicaslan, M.; Madavali, Babu; Hong, Soon-Jik (Springer Science and Business Media LLC, 2014)
In this study, n-type 95 %Bi2Te3-5 %Bi2Se3 thermoelectric materials have been produced by a combined process of gas atomization with subsequent magnetic pulsed compaction and spark plasma sintering, and then we investigated the behavior of transport properties with sintering temperature. The microstructural observation was performed by optical microscopy and scanning electron microscopy. The crystal structures were analyzed by X-ray diffractometer. The mechanical properties were calculated by measuring the density and micro-Vickers hardness of the samples. It was found that with increasing sintering temperature the gaps between powder particles decreases and the grain sizes were coarsened. The mechanical properties shows higher values along the parallel direction compared to the perpendicular direction to the pressing. The transport properties of the thermoelectric material were investigated with variation of the sintering temperatures. The maximum power factor 1.7 × 10−3 Wm−1 K−2 was measured at the sintering temperature of 450 °C.
Keywords: 7. Clean energy